2017
DOI: 10.1177/0885328217713354
|View full text |Cite
|
Sign up to set email alerts
|

Putty-like bone fillers based on CaP ceramics or Biosilicate® combined with carboxymethylcellulose: Characterization, optimization, and evaluation

Abstract: Calcium phosphates and bioactive glass ceramics have been considered promising biomaterials for use in surgeries. However, their moldability should be further enhanced. We here thereby report the handling, physicochemical features, and morphological characteristics of formulations consisting of carboxymethylcellulose-glycerol and hydroxyapatite-tricalcium phosphate or Biosilicate® particles. We hypothesized that combining either material with carboxymethylcellulose-glycerol would improve handling properties, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
(89 reference statements)
0
2
0
1
Order By: Relevance
“…Bio particles are highly bioactive and undergo a rapid multistage surface reaction when in contact with an aqueous media, ultimately resulting in the formation of hydroxycarbonate apatite. 15 Therefore, ET with Bio was not formulated with water or simulated body fluid; instead, it was formulated with CMC and glycerin as a vehicle 28 and was exposed to water only immediately before the simulated brushing. Furthermore, despite their high bioactivity, Bio particles take some time to completely dissolve, as observed in a previous study 29 and confirmed in our study through SEM analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Bio particles are highly bioactive and undergo a rapid multistage surface reaction when in contact with an aqueous media, ultimately resulting in the formation of hydroxycarbonate apatite. 15 Therefore, ET with Bio was not formulated with water or simulated body fluid; instead, it was formulated with CMC and glycerin as a vehicle 28 and was exposed to water only immediately before the simulated brushing. Furthermore, despite their high bioactivity, Bio particles take some time to completely dissolve, as observed in a previous study 29 and confirmed in our study through SEM analysis.…”
Section: Discussionmentioning
confidence: 99%
“…16 Although bioglasses have bioactivity, the handling properties of these materials for clinical use are limited. 17 Therefore, the association of Biosilicate powder with a hydrosoluble polymer 18 and carboxymethylcellulose 17 have been proposed in order to improve consistency and applicability.…”
mentioning
confidence: 99%
“…GABBAI-ARMELIN et al, 2017). Os vidros têm se mostrado promissores para a formação da hidroxiapatita ou fluoroapatita, como demonstrado em vários estudos (GJORGIEVSKA et al, 2013;KOHDA et al, 2015;MEHTA et al,.…”
unclassified